Supplementation of native grass hay with cowpea (Vigna unguiculata) hay, wilted leucaena (Leucaena leucocephala) forage, wilted tagasaste (Chamaecytisus palmensis) forage or a wheat middling for young Friesian x Zebu (Boran) crossbred steers - Varvikko, Tuomo; Khalili, Hannele; Crosse, S. (Agricultural Research Centre of Finland, 1992)
Sata päivää kestäneessä kasvukokeessa, joka tehtiin 40 friisiläis-zebu -risteytyssonnivasikalla, verrattiin lehmänpapua (Vigna unquiculata), kahta esikuivattua Leguminosaerehupuuta, leucaena (Leucaena leucocphala) ja tagasaste (Chamaecytisys palmensis), sekä vehnälesettä vasikoiden lisärehuna käytännön tilatason ruokinnassa. Valitut rehut ovat kotoperäisiä tai yleisesti paikallisesti luotettavia märehtijän rehuja tropiikin ja sub-tropiikin maissa. Lisärehua annettiin ilmakuivana 1.5 kg täydentämään luonnonvaraiseen niittyheinään perustuvaa ruokintaa, jossa myös päivittäinen kivennäisten saanti oli varmistettu. Johtopäätös kokeen syönti- ja kasvutuloksista oli, että vehnäleseen jälkeen tuotantovaikutukseltaan paras lisärehu oli leucaena. Toinen rehupuu tagasaste antoi huonoimman kasvutuloksen, kontrolliryhmä mukaan lukien. Huono kasvutulos ehkä johtui suureksi osaksi siitä, että eläimet jättivät noin kolmasosan tarjotusta tagasastesta syömättä. Muilla lisärehuilla ei havaittu syönti- tai maittavuusongelmia. Selostettu koe tehtiin Afrikan kansainvälisessä kotieläintutkimuskeskuksessa ILCA:ssa, Addis Abebassa, Etiopiassa. Koe on osa Suomen Ulkoasiainministeriön Kehitysyhteistyöosaston rahoittamaa lypsykarjan ruokinnan kehittämisprojektia Etiopian ylänköalueilla.

A 100-day experiment of a randomized block design was conducted with forty Friesian x Zebu (Boran) crossbred growing steers to compare the value of wheat middling, an agro-industrial by-product (diet W), cowpea (Vigna unguiculata) hay (diet C), and wilted forages of leucaena (Leucaena leucocephala, diet L) and tagasaste (Chamaecytisus palmensis, diet T) as cattle feed. These feeds were fed daily at a level of 1.5 kg (on an air dry basis) to supplement the basal diet (diet H) of native hay. A mineral supplement containing 50 g bone meal and 10 g common salt was also given daily. The steers were group-fed, but during the last two weeks at the end of the experiment the animals were housed individually in feeding pens to estimate the feed intake and apparent digestibilities of the diets. The animals were weighed at the beginning of the experiment, thereafter every two weeks, and finally at the end of the experiment. The animals consumed all the offered supplements, except for tagasaste forage, of which one third remained unconsumed. The mean daily total dry matter intake during the individual feeding period ranged from 4.0 to 5.0 kg between the diets (P<0.01). As to metabolizable energy and crude protein intakes, diet W ranked first, followed by diets L, C, T and H in descending order. The daily weight gain (g) was highest on diet W (41 1) again followed by diets L (37 1), C (236), H (86) and T (62). It was concluded that poor palatability may be a major problem in feeding tagasaste to growing cattle.
Yhteistutkimus MTT:n kanssa
Keywords: Ko; risteytyshärät; friisiläinen x zeba; kasvatuskokeet; nautakarja; leucaena; tagasaste; cowpea; wheat middling; growing steers